Sistema Operacional: levantamento dos problemas no setor de manutenção para implantar uma gestão adequada na área de manutenção de uma indústria de produtos de linha branca - Maciel, Antonio Carlos Walter (2014)
This paper discusses the organization and structuring of a maintenance system for the purpose of putting into practice the management of maintenance and track your benefits to justify the project, a search for reputable bibliographies will be held to contribute to the learning management systems maintenance and operation of the maintenance strategy. A proposal by the management to be deploying system is presented, showing a sequence of structuring. Is to use some basic aspects that act as pillars, intended to be used as support for the managerial model, the basic practices are needed to manage the system, 5s program, planned maintenance, the skilled and motivated employees, creation of indicators and targets. Aiming to unite practice with theory which was acquired in the course of specialization maintenance manager cooked UTFPR used as a basis for learning, a case study on a branch Industries refrigeration, a case study will be used containing a detailed description the tasks to be performed.